Website-Based STEM Learning Using Encyclopedias for Students with Special Needs - Ilham Saifudin; Wiwik Suharso; Syahrul Mubaroq (JUSTINDO (Jurnal Sistem dan Teknologi Informasi Indonesia), 2026)
In the world of education, we continue to create and innovate to improve the learning process and achieve desired learning outcomes. One of them is using digital-based learning (Digital Learning) which can be accessed with information technology. This research aims to determine the response to implementing a video blog-based learning system with a STEM (Science, Technology, Engineering, and Mathematics) approach. Apart from that, students will be given assignments using the Encyclopedia Website tool which contains formulas and logical flows related to Algorithms and Complexity courses. This will produce meaningful, quality learning that can be used by the wider community, especially to make it easier for students with special needs to learn to compile a simple algorithm. The method applied in implementing a website for students with special needs is a usability test with Nielsen' Attributes of Usability (NAU). Researchers carry out website evaluations with the aim of measuring and knowing the level of success of the website, how easy it is for users to understand. The research results showed that (1) the usability test with Nielsen' Attributes of Usability (NAU) can be used to measure the quality of website usability; (2) testing success rate of 100% because there were no failures in testing the search feature. Testing found a test pattern, namely that the more search keywords there are, the greater the number of document links produced, and the time required, however, it can significantly increase the highest similarity value of 0.21; (3) the respondents' conclusions show that the learnability, memorability, efficiency, errors attributes have an average helpful conclusion of 11, while the Satisfaction attribute has a very helpful average conclusion of 7.